2021
DOI: 10.1111/imr.13021
|View full text |Cite
|
Sign up to set email alerts
|

Sequence determinants as key regulators in gene expression of T cells

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 252 publications
1
13
0
Order By: Relevance
“…UTR length alone, however, is unlikely to be the sole factor that influences mRNA and protein abundance. Similar to the increased presence of ARE clusters in longer 3’UTRs [26], the overall likelihood of containing regulatory motifs and structures increases with length. Notably, murine T cells activated for 48h with aCD3/CD28 beads display substantial shortening of 3’UTRs [46].…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…UTR length alone, however, is unlikely to be the sole factor that influences mRNA and protein abundance. Similar to the increased presence of ARE clusters in longer 3’UTRs [26], the overall likelihood of containing regulatory motifs and structures increases with length. Notably, murine T cells activated for 48h with aCD3/CD28 beads display substantial shortening of 3’UTRs [46].…”
Section: Discussionmentioning
confidence: 87%
“…Untranslated regions of RNAs are critical components in defining the RNA levels and the protein output of a given mRNA, and the length of 5’UTR and 3’UTRs is contributing [26]. We therefore also compared the length of 5’UTRs and 3’UTRs across gene classes, and found that they show similar patterns (Fig 3B, C).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Untranslated regions of RNAs are critical components in defining the RNA levels and the protein output of a given mRNA, and the length of 5’UTR and 3’UTRs is contributing [ 34 ]. We therefore also compared the length of 5’UTRs and 3’UTRs across gene classes, and we found that they show similar patterns ( Fig 3B and 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…This impacts development of diseased states like cancer, allergy, inflammation, neurological disorders, maintenance of cellular homeostasis by autophagy, etc. [3,7,9,10,37]. In the present collection, Ghosh Roy has discussed about how wide range of diseases like cardiovascular, renal and gastrointestinal disorders to cancers like glioblastoma and neurodegenerative diseases; related to autophagy can be understood in the light of miRNA [47].…”
Section: Molecular Interactome and It's Role In Epigenetic Regulationmentioning
confidence: 99%